The Relationship Between Mother's Knowledge and the Nutritional Status of Children Aged 6-24 Months at the Labuhan Rasoki Community Health Center, Padang Sidimpuan City in 2024 - Oktavia, Nadia; Sari Lubis, Mutia; Aswan, Yulinda (Journal of Nutrition and Public Health, 2026)
Background: Chronic malnutrition has a significant impact on a child's physical growth, where feeding methods that are not appropriate to their age and nutritional needs are often caused by a lack of knowledge from mothers. Aims: This study aims to determine the relationship between maternal knowledge and the nutritional status of children aged 6-24 months at the Labuhan Rasoki Community Health Center, Padangsidimpuan City, in 2024. Methods:This type of research is quantitative with a cross-sectional approach, involving a sample of 70 respondents taken using a total sampling technique from the population of mothers who have children aged 6-24 months. Result: The results of the analysis using the Fisher Exact Test statistical test showed a p value of 0.000 (p < 0.05), which indicates that there is a significant relationship between maternal knowledge and children's nutritional status. Conclusion: It can be concluded that the level of maternal knowledge is closely related to the nutritional status of children aged 6-24 months in the working area of ​​the Labuhan Rasoki Health Center in 2024.